PENGEMBANGAN VIDEO TUTORIAL PEMBELAJARAN BULUTANGKIS UNTUK MENINGKATKAN KETERAMPILAN BERMAIN BULUTANGKIS SISWA DI SMAS BUQ’ATUN MUBARAKAH PONDOK PESANTREN DARUL AMAN GOMBARA MAKASSAR - Indi, Arindi Nurul Amalia Asman; Abd Haling; Farida Febriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted based on preliminary observations in which the researcher found that the badminton learning process at SMAS Buq’atun Mubarakah Darul Aman Gombara Makassar had not yet utilized interactive learning media, and was still dominated by conventional teaching methods. The objectives of this research are: (1) To identify the need for the development of badminton tutorial videos, (2) To design a badminton tutorial video that aligns with students' learning needs, and (3) To determine the validity and practicality level of the developed video. This research used the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). Data collection techniques used were questionnaires and documentation. The study involved 30 students and 1 physical education teacher. The results of the study are as follows: (1) In the define stage, the needs analysis indicated that students required audiovisual-based learning to better understand basic badminton techniques. (2) In the design stage, the tutorial video was developed by incorporating relevant content such as text, images, and video demonstrations based on the identified needs. (3) In the development stage, alpha testing showed that expert validation resulted in a score categorized as very valid. Media experts rated the video as highly appropriate, and content experts gave a score of 92%, placing it in the "very good" category. Beta testing in the small group trial yielded a practicality score of 90.1% (very practical), while the large group trial reached 96% (very practical). Additionally, feedback from the subject teacher also indicated the video tutorial was "very practical" for use in the learning process.